Center conditions for a cubic differential system with one invariant straight line and one invariant conic - Dumitru Cozma (Acta et Commentationes: Ştiinţe Exacte şi ale Naturii)
In this work we find the center conditions for a cubic system of differential equations with a critical point of a center or a focus type having one invariant straight line and one invariant conic. The center-focus problem is studied by using the Darboux integrability and the rational reversibility methods.